2011
DOI: 10.1038/hr.2011.78
|View full text |Cite
|
Sign up to set email alerts
|

Lower aerobic capacity was associated with abnormal intramuscular energetics in patients with metabolic syndrome

Abstract: Lower aerobic capacity is a strong and independent predictor of cardiovascular morbidity and mortality in patients with metabolic syndrome (MetS). However, the mechanisms are not fully elucidated. We tested the hypothesis that skeletal muscle dysfunction could contribute to the lower aerobic capacity in MetS patients. The incremental exercise tests with cycle ergometer were performed in 12 male patients with MetS with no habitual exercise and 11 age-, sex-and activity-matched control subjects to assess the aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 30 publications
(23 reference statements)
2
41
0
2
Order By: Relevance
“…In fact, lean body aerobic capacity was significantly lower in sedentary men with MetS, compared to controls with matched levels of physical activity [30]. A delimitation of our study, then, was that participants exercised at the same relative, rather than absolute, intensity, which we deemed a “fairer” comparison.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, lean body aerobic capacity was significantly lower in sedentary men with MetS, compared to controls with matched levels of physical activity [30]. A delimitation of our study, then, was that participants exercised at the same relative, rather than absolute, intensity, which we deemed a “fairer” comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies unequivocally indicate that exercise training (ET) is an effective method in improving blood glucose regulation, insulin resistance, blood lipids, and blood pressure 57. The limited exercise capacity and impaired energy metabolism can also be improved, delaying the onset and progression of cardiovascular disease in patients with type 2 diabetes 8,9. In addition to exercise, a great body of evidence has shown that limiting food intake is an effective frontline strategy to reduce cardiometabolic risk and disorders 10,11.…”
Section: Introductionmentioning
confidence: 99%
“…Spectra were line broadened and phase and baseline corrected, and the resonances of interest were line fit at a mixed Lorentzian/Gaussian function. After correction for T1 and T2 relaxations, quantification of IMCL and EMCL content was carried out to compare intensity of (CH2) n (methylene) at 1.3 ppm and 1.5 ppm resonance to the water resonance intensity at 4.7 ppm (Figure 1) [15][16][17][18]. The IMCL and EMCL values were corrected for multiple CH 2 groups by using the methods described by Szczepaniak et al [4].…”
Section: Methodsmentioning
confidence: 99%